Innovation based learning contextual for thermochemistry topic in senior high school - Nurhayani Nurhayani; Marini Damanik; Marudut Sinaga (Jurnal Pendidikan Kimia (JPKim), 2018)
The implementation and development of teaching materials purposed to find the topic based on the criteria of National Education Standard Agency (BSNP). The student learning outcomes increase in thermochemistry topic based on the modules contextual. The population in this study were all students of class XI MIA SMAN 2 Percut Sei Tuan consists of 4 classes, while the students of each class were ± 35 people. The sample used in this study consists of two classes randomly selected. The first class as the experimental which given learning module as a contextual-based teaching materials, however the control class was given without it. The instrument used assessment BSNP that shared to 1 teacher and 2 lecturers. The test used multiple-choice with 20 questions that were valid and reliable. As a prerequisite for testing, the hypothesis of learning outcomes both groups of samples were tested for homogeneity using programs Microsoft Excel. The results of the study showed that teaching materials met BSNP criteria that content = 4.16; language = 4.14; presentation = 4.04; Integrity = 4.18 by lecturer. Furthermore, the data achieved of content = 4.32; language = 4.21; presentation = 4.20; integraty= 4.13 by teacher. There are valid criteria and no need revision. The tests performed two sample groups were homogeneous. Hypothesis testing is done by using Paired Sample T-Test with SPSS 21. The hypothesis test concludes that the chemical learning outcomes of students uses teaching materials contextual-based module is higher than the student learning outcome without it in the thermochemistry module.Keywords:contextual; module teaching materials; outcomes learning